2023
DOI: 10.1002/job.2706
|View full text |Cite
|
Sign up to set email alerts
|

Collective friend group reactions to organizational change: A field theory approach

Abstract: SummaryThis paper integrates field theory with a social network perspective to show that perceptions of the quality of the organization's change communication become collectively shared in friend groups, and that these collective perceptions positively influence collective job performance in those friend groups. Findings from two studies show that these collective perceptions influence collective performance both directly and by interacting with change history in friend groups. The results extend theory by hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Although the strength of ties in a changing context was not tested directly by any of the papers in this special issue, this is an area that holds promise and could be further explored. Indirectly, Vardaman et al (2023) in this special issue found empirical support for the role of friendships (a potential proxy for strong ties) in shaping up collective responses to change.…”
Section: Mechanismsmentioning
confidence: 94%
See 4 more Smart Citations
“…Although the strength of ties in a changing context was not tested directly by any of the papers in this special issue, this is an area that holds promise and could be further explored. Indirectly, Vardaman et al (2023) in this special issue found empirical support for the role of friendships (a potential proxy for strong ties) in shaping up collective responses to change.…”
Section: Mechanismsmentioning
confidence: 94%
“…Given the pervasiveness of the psychological perspective in change response research, the number of papers with a sociological lens is less strongly represented in our special issue. Only two papers adopted a sociological lens (i.e., Pallotti et al, 2023;Vardaman et al, 2023). Both papers are inspired by mechanisms that Schwarz and Bouckenooghe (2018) use for explaining the relationships between individual and collective responses to change, specifically, network contagion, and its structural building blocks network type, and strength of ties/connections.…”
Section: Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations